Criminological and victimological determinants of prostitution: De lege ferenda proposals - Pavlović Zoran; Petković Nikola (Glasnik Advokatske komore Vojvodine)
Prostitution represents a complex social phenomenon, often integrating criminological and victimological perspectives. Positioned between the ideas of sexual freedom, the right to control one's own Pbody, and the obligation to protect morality, prostitution elicits various societal responses. Discussing the concepts of authentic and apparent prostitution, the authors aim to provide a conceptual analysis and a draft of a new legislative model for regulating this field. By integrating sociopsychological and health care tendencies, minimizing stigmatization and discrimination, the stratified societal response model is presented, which ultimately does not abandon the protection of morality as a legal and social category and a vital societal component.